PREDISOPSING FACTORS; MANAGMENT AND OUTCOMES OF NECROTIZING FASCITIS Among patients who admitted to surgical ward at Al-Thawra hospital; January 2020 to January 2021 - Obadiel, Yasser Abdurabo; Alyan, Mohammed Hamood (Journal of medical and pharmaceutical sciences, 2021)
Background: Necrotizing fasciitis is a serious infection of skin and soft tissues that rapidly progresses along the deep fascia. It’s a fatal infection with high mortality if treatment delayed. Early diagnosis, surgical debridement and broad-spectrum antibiotic therapy are the optimal treatments to reduce the mortality. Objective: The aims were to identify risk factors for Necrotizing fasciitis and to describe the outcome of management. Methods: A prospective descriptive study was conduted at AL-THAWRA HOSIPTAL located in Sana’a, Yemen. All medical records of patients with confirmed NF who admitted to surgical department between January 2020 and January 2021 were reviewed. Results: The study enrolled 54 patients diagnosed with Necrotizing fasciitis. Male patients were 43 patients (79.6%) and female patients were 11 patients (20.3%). The age rang was 9 – 75 years old and the peak age incidence was at 46–60 years (33.3%). The incidence of NF increases with aging, male gander (79.6%), in comorbid patients (64.9%) especially DM (37%). The etiologies of NF were trauma in (16.6%) and perianal abscess in (14.8%), but (27.7%) of NF patients hadn’t specific cause. The defected wound was treated by skin graft in (32.5%) and primary closure in (27.5%). The mortality rate was (27.7% n=15); (60%) of them died on first 5 days. Septic shock was the reason of death in (73.2%). The higher mortality rate was seen at male gander (66.6%), age group > 60 years (46.6%), in patients who presented in shocked state (73.3%) and in comorbid patients (73.3%). Conclusion: Necrotizing fasciitis represents a life threatening condition with challenges in diagnosis. Incidence and mortality of NF are common in male gander, an elderly patient, or in who suffers of comorbidities; especially DM.
Keywords: Necrotizing fasciitis; Outcomes; Factors; Yemen